High prevalence of primary headaches among patients with post-traumatic stress disorder: an observational study of consecutive patients - Hugues Magne; Bruno Pereira; Xavier Moisset (The Journal of Headache and Pain)
Abstract Background Primary headaches affect between 40% and 50% of people worldwide and are linked to a range of medical and mental health conditions, including post-traumatic stress disorder (PTSD). Our objective is to assess the prevalence of primary headaches in individuals with PTSD, identify the types, timing, and impact of traumatic experiences, and compare this prevalence to that of the general population. Methods This descriptive, retrospective observational study included 302 patients. Each participant was initially assessed using the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5) PTSD criteria, the Post-Traumatic Stress Disorder Checklist for DSM-5 (PCL-5), the International Classification of Headache Disorders, 3rd edition (ICHD-3) for headache classification, and the Hospital Anxiety and Depression Scale (HADS). Both type 1 and type 2 trauma, whether occurring in childhood or adulthood, were identified, along with the nature of the trauma. Results The age of the population was 42 ± 14 years, with a PCL-5 score of 47.6 ± 9.9. A total of 77% of patients were diagnosed with primary headaches, including 47% with tension-type headaches (TTH) and 30% with migraines. Chronic migraine sufferers reported significantly higher rates of childhood trauma (71%), while episodic migraineurs showed similar rates of both childhood and adult trauma. Chronic TTH patients experienced more childhood trauma (91%) compared to adulthood trauma, whereas episodic TTH patients reported a higher incidence of adulthood trauma than childhood trauma. The majority of childhood traumas were of type 2 and intrafamilial origin, with 45% of patients reporting sexual abuse, 51% physical abuse, and 4% other types of trauma. In the adulthood trauma group, 34% reported sexual abuse, 40% physical abuse, and 26% other forms of trauma, with a notably high rate of intimate partner abuse (both type 1 and type 2). We observed significantly higher rates of migraine (OR = 1.59, 95% CI: 1.23–2.05) in our cohort compared to the general population, with particularly higher prevalences in men and older patients. A significant association was found between childhood trauma and the presence of chronic headache in the overall headache cohort and in patients with TTH. However, no statistically significant association was observed among patients with migraine. Conclusions Patients with PTSD exhibit a higher prevalence of primary headaches, likely due to childhood trauma. Headache specialists should routinely screen for trauma and offer tailored treatments to address these underlying factors.